2016
DOI: 10.1111/tbj.12627
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Contrast-Enhanced Spectral Mammography in Postscreening Assessment

Abstract: To assess the value on diagnostic and treatment management of contrast-enhanced spectral mammography (CESM), as adjunct to mammography (MG) and ultrasound (US) in postscreening in a breast cancer unit for patients with newly diagnosed breast cancer or with suspicious findings on conventional imaging. Retrospective review of routine use of bilateral CESM performed between September 2012 and September 2013 in 195 women with suspicious or undetermined findings on MG and/or US. CESM images were blindly reviewed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…After a systematic search of the relevant electronic databases, 534 publications were initially identified, and after removal of duplicated data, studies and noncorrelated studies, 13 diagnostic publications were identified and included in the final meta‐analysis (Fig ). Of those included, five were retrospective studies and the other eight were prospective work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a systematic search of the relevant electronic databases, 534 publications were initially identified, and after removal of duplicated data, studies and noncorrelated studies, 13 diagnostic publications were identified and included in the final meta‐analysis (Fig ). Of those included, five were retrospective studies and the other eight were prospective work.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) for the detection of breast lesions has also been proven to be effective with relatively high sensitivity. Several studies have previously compared the diagnostic performance of CESM and MRI in breast cancer screening. However, the conclusions of these studies were different because of the small sample size and study designs.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have suggested promising future applications in diagnostics, therapy follow-up, and 'high-risk' patient screening. [21][22][23] Clinical studies have suggested that the lesion detection capability is significantly superior for contrastenhanced mammography than conventional mammography and ultrasound using BI-RADS lexicon in the diagnostic workup. 24,25 A recent study suggested that when used with conventional mammography, contrast-enhanced mammography was able to increase the sensitivity in detecting malignancies from 78% to 93%.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, CESM still deserves evaluation and the results of this meta-analysis cannot be considered as conclusive. Interestingly, two recent studies confirmed a high sensitivity of CESM (94–95 %) with higher values of specificity: 81 % in the symptomatic setting [35] and 74 % in the post-screening assessment [36]. …”
Section: New Mammographic Techniques: Tomosynthesis and Contrast-enhamentioning
confidence: 99%